Optimal distance geographic routing for energy efficient wireless sensor networks. (27th July 2006) - Huang, Xin-Ming; Ma, Jing
Wireless sensor networks require energy efficient routing protocols owing to limited resource on the sensor node. In this paper, we develop optimal distance geographic routing (ODGR), an application-independent algorithm that uses geographic information and power control in the transmission scheme to dynamically explore the optimal routing path. ODGR is derived from fundamental radio energy model to minimise total communication energy using convex theory. Case study on a two-dimensional array network shows that ODGR is able to reduce total communication energy by 66.41% and 43.89%, and average latency by 76.45% and 26.27%, when compared to traditional MTE and cluster algorithms.